Genotype x environment interaction effect and genotypic correlation for nutrient quality traits of indica rice (Oryza sativa) - SHI, C H; JHU, J; YU, Y G (The Indian Journal of Agricultural Sciences, 2013)
The genetic effects and genotype x environment interaction effect on nutrient quality traits of indica rice (Oryzasativa L.) was studied during 1994-95 by using genetic models for quantitative traits of triploid endosperm. Ninecytoplasmic male sterile lines as females and 5 restoring lines as males were included in a factorial design for 2 years.Results indicated that the nutrient quality traits of protein content, protein index and lysine content were mainlycontrolled by genetic effect but lysine index was mainly affected by genotype x environment (OE) interaction effects.Maternal effects were the main genetic effects for protein content, lysine content and lysine index, hut not for proteinindex. Cytoplasmic effects were significant for protein content and protein index only. Among the GE interaction effects,protein content and lysine content traits were mainly affected by seed interaction effects and protein index and lysineindex by maternal interaction effects. Direct additive and maternal additive effects primarily controlled tbe performanceof the rice nutrient quality traits. Direct and maternal additive interaction effects were more important ror protein contentand protein index. The nutrient quality traits were controlled by direct and maternal dominance effects, and theirenvironment interaction effects especially for lysine content and lysine index. The cytoplasmic interaction effects weresignificant for all nutrient quality traits studied. The genotypic correlations among nutrient quality traits could be furtherpartitioned into genetic correlations and GE interaction correlations. Significant correlations for the parirwise nutrientquality traits, especially for direct additive correlations and cytoplasmic interaction correlations, Were noted.